Art-based narrative inquiry with Native American breast cancer survivors - Warson, Elizabeth, author; Kees, Nathalie, advisor; Carlson, Laurie, advisor (Colorado State University. Libraries, 2008)
Background and aims. Breast cancer rates for American Indian and Alaska Native women are lower than any ethnic or racial group. This fact alone has contributed to the perception that breast cancer is not an "Indian" problem among health officials. Cancer statistics in general for American Indian and Alaska Natives are unreliable because of the frequency of racial misclassification, underreporting, and clustering data under the "other" category. Inclusive data from The Intercultural Cancer Council suggests that rates of breast cancer for American Indians and Alaska Natives, who experience the poorest 5-year survivorship, have been increasing over the past 20 years. The majority of the cancer research among Native people has concentrated on eliminating social, cultural, and structure barriers to healthcare. What has not been included in the literature are culturally-relevant psychosocial interventions incorporating the expressive arts. Behavioral research in cancer care for Native American women is needed to address quality of life factors. The purpose of this post modern narrative inquiry is to explore, through artmaking and storytelling, the belief systems surrounding wellness and physical illness from the perspective of Native women diagnosed with breast cancer. This narrative inquiry would provide the ground work for culturally-competent psychosocial interventions utilizing the expressive arts. Method. The participants were 2 American Indian women diagnosed with breast cancer from the Coharie tribe in Clinton, North Carolina, ages 74 and 66. These women were co-collaborators in an emergent narrative inquiry, incorporating a demographic interview, 3 main art task, and 8 open-ended interview questions. Their stories were analyzed discursively using the zoom model. To supplement the emergent themes from the analysis, 3 additional data sources, comprising interviews from a traditional healer and two tribal representatives, were included in the situational analysis. Results. Two positional "maps" were created from the layers of narrative and visual discourse analysis. The maps charted different positions along a four different continuums: cancer related medical treatment, traditional American Indian healing practices, wellness, and breast cancer and breast cancer treatment. The maps showed that wellness and spirituality were inseparable and a core belief to undergoing breast cancer treatment and survivorship. Traditional healing practices were viewed as a complementary approach to Western medicine; however, this approach was not a shared position with providers. The positional maps suggested that a more culturally-relevant, holistic, approach to cancer care was needed in this community.
Keywords: art-based; breast cancer; narrative inquiry; Native American; school counseling; Native American studies